Care plan for pregnant and postpartum woman with diagnosed cancer – metastatic lymphoma - Lesińska, Martyna W.; Czerwińska-Osipiak, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2023)
The diagnosis of a disease in a patient such as mediastinal lymphoma leads to complications and a sharp drop in mood. A skilled midwife can provide holistic and individualised care for both healthy and sick women. In caring for pregnant and postpartum women diagnosed with mediastinal lymphoma, the midwife undertakes care and education intervention aimed at improving the patient’s comfort and self-care skills. Implementing the assumed measures eliminates risk factors for the occurrence of care problems, providing support for the woman during the disease. The aim of the paper is to present the plan of care provided to a pregnant and postpartum woman diagnosed with mediastinal lymphoma based on an individual case study. For the creation of this study a “study case” research method was used. Informed consent was obtained in the study. The C-HOBIC care outcome indicators and reference terminology were used during the case report.